Understanding the African growth record: The importance of policy syndromes and governance - Augustin Kwasi Fosu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
The current paper, first, finds that although the post-independence growth of African economies has fallen substantially below that of other regions, this comparative evidence is less than uniform across time and countries. Second, it uncovers total factor productivity as the primary culprit underlying the generally dismal growth record. Third, reflecting recent evidence, the paper finds that policy syndromes represent a major culprit explaining the growth performance, with their absence accounting for nearly 3.0 percentage point rise in the annual per capita GDP growth via increases in TFP. Finally, the paper finds that governance exerts positive direct and indirect impacts on growth; the latter is via the potential ability of governance to achieve a syndrome-free regime.
Keywords: O11; O43; O55; 330; African growth; policy syndromes; governance